Analysis of partner of inscuteable, a novel player of Drosophila asymmetric divisions, reveals two distinct steps in inscuteable apical localization. - Yu, F.; Morin, X.; Cai, Y.; Yang, X.; Chia, W. (Cell, 2000)
Asymmetric localization is a prerequisite for inscuteable (insc) to function in coordinating and mediating asymmetric cell divisions in Drosophila. We show here that Partner of Inscuteable (Pins), a new component of asymmetric divisions, is required for Inscuteable to asymmetrically localize. In the absence of pins, Inscuteable becomes cytoplasmic and asymmetric divisions of neuroblasts and mitotic domain 9 cells show defects reminiscent of insc mutants. Pins colocalizes with Insc and interacts with the region necessary and sufficient for directing its asymmetric localization. Analyses of pins function in neuroblasts reveal two distinct steps for Insc apical cortical localization: A pins-independent, bazooka-dependent initiation step during delamination (interphase) and a later maintenance step during which Baz, Pins, and Insc localization are interdependent.